Comparing life cycle energy and global warming potential of carbon fibre composite recycling technologies and waste management options - Meng, Fanran; Olivetti, Elsa A.; Zhao, Youyang; Chang, Jiyoun C.; Pickering, Stephen J.; McKechnie, Jon (2018)
Carbon fibre reinforced polymers (CFRP) are used in increasing quantities as they have some of the best properties in terms of specific strength and stiffness of any widely available material. By 2020, annual global CFRP production is expected to be over 140,000 tonnes. However, the resulting increased quantity of CFRP waste has highlighted the need for sustainable treatment options as carbon fibre manufacture has high-energy intensity. A life cycle methodology is used to evaluate primary energy demand (PED) and global warming potential (GWP) leveraging best available literature data, process models, and experimental work. Overall results indicate that recycling scenarios are generally the environmentally preferable options over landfill and incineration. However, the relative environmental benefits of advanced recycling processes (i.e., pyrolysis, fluidised bed, and chemical recycling process) depend on the method used to determine displacement of virgin carbon fibre by recycled carbon fibre. Totally, recycling processes can achieve a representative GWP of -19 to -27 kg CO2eq. and PED of -395 to -520 MJ per kg CFRP, providing superior environmental performance to conventional composite waste treatment technologies.